Compared nymphal development of Tingis americana (Hemiptera, Tingidae) in two Handroanthus species (Bignoniaceae) and reproductive parameters in seedlings of Handroanthus heptaphyllus - Daiane C. Moreira; Luiza R. Redaelli; Marcus Guidoti; Aline Barcellos (Iheringia: Série Zoologia, 2013)
Nymphs and adults of Tingis americana Drake, 1922 were found feeding on leaves of Handroanthus heptaphyllus (Vell.) Mattos and Handroanthus chrysotrichus (Mart. ex A. DC.) Mattos in the Botanic Garden, Porto Alegre, state of Rio Grande do Sul, Brazil. This is the first record of T. americana on these host plants and in the southern Brazil. We aimed to compare the nymphal development on both hosts and to analyze the reproductive parameters on H. heptaphyllus (25 ± 1ºC; 60 ± 10% RH; 16 h photophase). The mean nymphal period (days) was shorter in individuals reared on H. heptaphyllus (12.69 ± 0.076) than on H. chrysotrichus (19.11 ± 0.208) (P < 0.0001), however, nymph viability was similar. On H. heptaphyllus, the mean embryonic period lasted 12.32 ± 0.274 days and the egg viability was 92%. The mean total and daily fecundity were 310.0 ± 19.40 eggs/female and 7.46 ± 0.302 eggs/female/day, respectively. Paired males and females showed similar longevity (P = 0.0691), while unpaired females lived longer than unpaired males (P = 0.0460).